A Combined System of Ground Well and Composted Olive Cake for Hot Water Production at Olive Mills - Mohamad I. Al-Widyan; Taha M. Rababah; Majdi Al-Mahasneh (Journal of Food Quality)
Building a system that consists of a combination of geothermal component (water well (pit)) and heat recovery from aerobic biological fermentation of olive cake for hot water production at an olive mill is examined in this work. Hot water is essential for mill operation and constitutes a main operational cost, and in many countries, including Jordan, it is normally produced using diesel fuel. In this process, treated and untreated olive cake was characterized. Results show that olive cake is rich in crude fiber and NFE, contains moderate amounts of crude protein and fat, and a good amount of ash. The as-received moisture content ranged from 33.3 to 35.6%, while water activity was between 0.93 and 0.96. The total counts, thermophilic bacteria, and the total mold count of fermentation ranged, respectively, from 2.1 × 108 to 2.4 × 108, 1.7 × 104 to 1.9 × 104, and 1.5 × 102 to 1.7 × 102. The temperature results showed that the well and the covered tank led to a rise in water temperature before entering the boiler in the range of 7 to 13°C. The system effected significant raises in water temperature entering the boiler ranging from 19°C up to 25°C, which holds a promising potential for the system to satisfy much of the mills needs at this range of temperature before entering the boiler provided a large enough pile (pile scale up) is used to handle larger flow rates. The exhausted cake may well be utilized as a soil organic fertilizer.